Interactive multimedia for adaptive e-learning science for children / Zaleha Ismail - Ismail, Zaleha (2012)
Science is one of the important subjects at school. However, not all students interested to that subjects. Another problem is some teachers used learning method which is out dated. The aim of this research is to propose an interactive multimedia for adaptive e-learning Science for Children. The objectives of this research are to identify key elements of adaptive e-learning Science for children, to identify the key features of interactive multimedia for adaptive e-learning Science for Children, and to design and demonstrate interactive multimedia for adaptive e-learning Science for Children. The significant of this research is to help the teacher in delivering creativity in teaching and learning. A multimedia application for learning Science is viewed as important in order to help students especially children, to learn Science. This study proposes to design Interactive Multimedia of Adaptive E-learning Science for Children. It provides interactive games, and report and reward catalogues. This study aims to help children to interest to learn Science. Besides that, this research is also intended to produce a conceptual framework that can be guideline for Science learning.